The Huisgen’s cycloaddition of BODIPY acetylene and ferrocene azides in supercritical CO2 - Pavlov, Kirill G.; Guk, Dmitry A.; Burlutsky, Roman O.; Moiseeva, Anna A.; Krasnovskaya, Olga O.; Lemenovskiy, Dmitry A.; Zyk, Nikolay V.; Beloglazkina, Elena K. (Mendeleev communications, 2024)
[Display omitted] The copper-catalyzed azide–alkyne cycloaddition of BODIPY acetylene derivative and ferrocene azides in supercritical CO2 at 80 °C and 81 bar affords the corresponding triazole-containing BODIPY–ferrocene conjugates in high yields. The fluorescent and electrochemical properties of the compounds thus obtained were explored.